Evaluation of Protective Effect of Different Doses of Terminalia arjuna Bark Ethanolic Extract on Cisplatin Induced Oxidative Nephrotoxicity in Rats - Venkateshwarlu Eggadi; Sharath Chandra Korupozu; Bharath kumar Korupoju; Sharavanabhava Bandaru Sheshagiri; Shiva Kumar R; Venkateshwar Rao Jupally (College of Pharmacy University of Baghdad, 2017)
Cisplatin (CP), a platinum compound, is one of the most active cytotoxic drugs used for cancer treatment. Nephrotoxicity is severe dose limiting side effect of this drug. Abnormal production of reactive oxygen species (ROSs) leading to oxidative stress has been implicated in kidney toxicity by Cisplatin. Here the study was aimed to evaluate nephroprotective effect of ethanolic extract of Terminalia arjuna bark (EETAB) at the doses (200 & 400 mg/kg, body weight) against Cisplatin (7.5 mg/kg, i.p) induced nephrotoxicity in rats. The evaluation was done by measuring % change in body weight, renal function tests such as Blood Urea Nitrogen (BUN), Serum Creatinine (Cr), Serum Total Protein (TP) and also Kidney SOD (Superoxide dismutase),CAT (Catalase), GSH (Reduced glutathione) and MDA (Malondialdehyde) levels altered by Cisplatin administration. Rats treated with EETAB2 (400mg/kg) significantly (P<0.001) reduced the elevated levels of BUN, Cr, TP, MDA and significantly (P<0.001) increased the levels of SOD, GSH, and CAT by restoring kidney architecture. In conclusion EETAB2 (400mg/kg) attractively showed the protection against Cisplatin nephrotoxicity. Keywords: Cisplatin, Nephrotoxicity, Terminalaia arjuna, Reactive oxygen species, Renal function tests.